2011
DOI: 10.1111/j.1365-2214.2011.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional background and the comprehension of family‐centredness of rehabilitation for children with cerebral palsy

Abstract: Professional background and professional context seem to affect the apprehension of family-centred service. Also work experience and being part of a multidisciplinary team have an influence on how the professionals embrace the family-centred service delivered. The MPOC-SP can be used to identify areas for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 23 publications
5
29
1
2
Order By: Relevance
“…age, discipline, work status or forms of service organization) may also be associated with professionals' perceptions of their work with families (Camden et al ; Christon & Myers ). Our finding is consistent with previous research reporting that more experienced professionals tend to rate themselves higher than less experienced professionals (Dyke et al ; Mazer et al ; Raghavendra et al ; Jeglinsky et al ; Christon & Myers ). One explanation is that more experienced professionals might have higher self‐efficacy in implementing family‐centred practices and thus had higher perception about being family centred (Tang et al ; Christon & Myers ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…age, discipline, work status or forms of service organization) may also be associated with professionals' perceptions of their work with families (Camden et al ; Christon & Myers ). Our finding is consistent with previous research reporting that more experienced professionals tend to rate themselves higher than less experienced professionals (Dyke et al ; Mazer et al ; Raghavendra et al ; Jeglinsky et al ; Christon & Myers ). One explanation is that more experienced professionals might have higher self‐efficacy in implementing family‐centred practices and thus had higher perception about being family centred (Tang et al ; Christon & Myers ).…”
Section: Discussionsupporting
confidence: 93%
“…The ratings of professionals in our study provided initial support for cross‐cultural validity of the C‐MPOC‐SP. Overall, the findings indicate that participants in our study had positive views of their family‐centred practices and are comparable with ratings reported in studies conducted in paediatric rehabilitation settings in Finland (Jeglinsky et al ), the Netherlands (Siebes et al ) and Canada (Woodside et al ). In contrast, ratings by professionals of their family‐centred practices in a neonatal intensive care setting in Japan were lower than in our study (Himuro et al ).…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation for conductors scoring relatively low in this domain may be that providing general information in a multidisciplinary special education system is often the primary responsibility of the social worker. This explanation is supported by Woodside et al (), Raghavendra et al () and Jeglinsky et al (), where higher scores were given by social workers and psychologists in this domain. Another explanation for what seems to be a universal finding may be that service providers have significant demands placed on them and often have little time available with each family to discuss general information (Cunningham & Rosenbaum, ).…”
Section: Discussionmentioning
confidence: 61%
“…; Jeglinsky et al . , ; Wang et al . ), yet in other studies, additional domains were also identified as needing improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In our examination of the literature, MPOC‐SP proved to be a useful measure in the setting of traditional children's treatment centres . It was also used in other settings, including hospitals, children's hospitals, and community development programmes . MPOC‐SP was reported to be useful in gathering service providers' perceptions about their use of family‐centred practices; in identifying strengths and gaps in service delivery; and in comparing parents' perceptions with service providers' perceptions .…”
Section: Resultsmentioning
confidence: 99%